Mencapai Keselamatan - Kurniawan, Abimardha (Masyarakat Sejarawan Indonesia, 2017)
The conveyence of a collection of palm-leaf manuscripts , from Mt. Merbabu to Batavia in the middle of 19th century, must be seen in the context of the colonial government’s response to Islam after the Java War of 1825—1830. The Dutch authorities assumed that the manuscripts, which mostly use Buda script, came from a very old period, before Islam entered and spread throughtout Java. However, a few years after the manuscripts had been held in the Bataviaasch Genootschap library, it was realised that the manuscripts were produced at a time when Islam had become considerably entrenched in Java, around the 16th to 17th century. Nevertheless, although Islamic influence is clearly present, older cultural elements have still been preserved. Taking a Javanese text named Nabi Aparas as an example, it can be shown that the Islamic texts in this collection (as well as the other pre-Islamic texts in this collection), are concerned with the salvation of life.